Case report: Twice-daily 15mA transcranial alternating current stimulation for adolescent major depressive disorder with suicidal ideation - Cheng, Dan-dan; Yang, Yi-lin; Yuan, Zi-yi; Hong, Su; Kuang, Li (Frontiers in Psychiatry, 2025)
BackgroundAdolescent major depressive disorder with suicidal ideation (MDD-SI) poses significant treatment challenges and carries substantial mortality risk, while existing interventions often demonstrate limited acute efficacy for suicidal ideation (SI).MethodsThis two-week prospective case series investigated the feasibility and preliminary therapeutic effects of high-frequency transcranial alternating current stimulation (tACS) administered twice daily. Seven adolescents with MDD-SI underwent 40-minute tACS sessions (77.5 Hz, 15 mA) twice-daily over a two weeks for a total of 20 sessions, in conjunction with stable pharmacotherapy.ResultsThe accelerated tACS protocol was well-tolerated with no adverse events. It demonstrated significant reductions in both depressive symptoms and SI within two weeks (all P < 0.05), predominantly in the first week. Treatment response varied based on psychiatric and medical comorbidities, indicating potential moderators.ConclusionThese preliminary findings suggest the potential of accelerated high-frequency tACS as a potential crisis intervention for adolescent MDD-SI, while highlighting the need for controlled clinical trials to establish efficacy and optimize stimulation parameters.